Opportunities and Challenges of the Media Education Students at the Universities of Sri Lanka in Professional Internship Trainings - Raguram, S.; Sivatharshiny, P.; Dhulabarani, M. (My University, 2020)
Media education at the university level has completed more than 50 years of its introduction in Sri Lanka. At present, the systematic courses related to media and communication studies at under graduation, post-graduation and research programmes level have been conducted at eight National Universities all over the island. Apart from the Universities, the state media organizations such as Sri Lanka Broadcasting Corporation, State Television: Sri Lanka Rupavahini Corporation are also conducting short term courses and on the job training to enhance and update the knowledge and skills of their employees. In addition to this, the institutes that belong to the associations of privately owned professional media outlets such as Sri Lanka Press Institute also involve in conducting diploma and certificate courses for different fields of media education regularly and whenever necessary. It could be observed that the courses impart theoretical, practical and professional training they need. However, the students, the academics, and the industry people feel that the space for internship practice is not sufficient to meet the professionalism. In this context, this research focuses on finding whether the tasks on internship training assigned to the students of Universities meet the requirements of the objectives of the courses and the professional standards expected to enter into the world of work. The research investigates the process of the selection of media organizations for the internship, the tasks assigned during the period of training, the viability of the application of courses learned, the opportunities to enhance the capacity building of the students, the challenges and barriers faced by the internees, the observations, and the recommendations put forwarded by the industries, academics, and students as major stakeholders. This research has chosen the Trincomalee Campus of the Eastern University of Sri Lanka from the Eastern Province, the University of Kelaniya from the South, and the University of Jaffna from the North where the media, communication, and mass communication undergraduate courses available, as the research area. Further, the inquiry on the contribution of Sri Lanka Broadcasting Corporation, State Television: Sri Lanka Rupavahini Corporation, Country’s first television channel: Independent Television Network, Privately owned Maharajah Television / Broadcasting Channels and International Broadcasting Corporation – Tamil as the placement institutes of the internship was also included. The data obtained through the interviews and focus group discussions among the academics and the students of the three selected Universities and the scrutiny on the evaluation made by the institutions that provide professional training. The analysis was carried out quantitatively and qualitatively. The research found that the students preferred electronic media to print media for the internship, they developed the practical skills notably during the internship with the light of the theoretical foundation gathered from the Universities, and the course units: reporting techniques and skills, editing concepts and processes, production technologies, film studies, audio-visual editing, photojournalism, media management, and laws and ethics relevant to media functions were much help to create conducive environment to work with professionals. Further, the research identified the major opportunities through the internship to the students as the internship helps the student to adapt themselves to the new environment, placement to get familiar with a professionals, adaptation in a multicultural sphere, acquisition of new language/s, different openings in the professional world, and potential to work independently and empower them to start a media on their own with confidence, and the limited duration, non-payment of stipends, unfair treatment of the permanent employees, less space to acquire training in desired fields, lack of opportunity to learn the in-depth knowledge, the training that provides only the knowledge of the assigned section of and thus fails to help the students get the necessary know-how of the other areas of the field were identified as major challenges. The researcher obtained the following as recommendations; increasing the period of internship, teaching subjects related to languages, conducting more sessions of sharing experiences of professionals, providing more practicals according to the curriculum, and the universities taking the responsibility of paying stipend during the period of training and providing more training on media which the students are interested in at pre-internship period.
Keywords: Media Education; Internship; Media Outlets